Transactional Analysis as A Tool for Managing Remote Employees: The Application of Psychological "Hungers” Analysis - Agata Branowska; Michal Weres (Communications of International Proceedings, 2024)
The article examines the continued relevance of Transactional Analysis (TA) as a tool for addressing challenges faced by managers in the modern workplace. The authors focus specifically on the rise of remote work arrangements, which became much more common after the start of the COVID-19 pandemic. The article analyzes how this new working arrangement affects the ability of managers to satisfy the needs of their employees. To do this, the authors use Eric Berne's concept of three basic psychological hungers or needs: stimulation, recognition, and structure. The article argues that remote work makes it more difficult for managers to meet these needs, but it also opens up new possibilities for doing so. In spite of being a theory from the 1950s, TA is still a useful tool for managers who are trying to address the challenges of today's workplaces.
Keywords: transactional analysis; hunger analysis; remote work; hybrid work